Tauhid-Based Integral Education and Student Academic Achievement: A Case Study at SMP Luqman Al-Hakim Surabaya - Mustakim Noreng; Alfi Syahrin; Benny Prasetiya (PT. Caesarindo Triloka Persada, 2026)
Contemporary Islamic education faces the challenge of integrating academic achievement with spiritual and character formation. This study examines the implementation of Tauhid-Based Integral Education (TBIE) at SMP Luqman Al-Hakim Surabaya and explores how this model supports students’ learning motivation, academic character, and achievement orientation. A qualitative descriptive case study design was employed. Data were collected through participant observation, semi-structured interviews with school leaders, teachers, and students, and documentation of curriculum materials, lesson plans, school programs, and achievement records. The data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion verification, with credibility strengthened through triangulation, member checking, and peer debriefing. The findings show that TBIE is implemented as an epistemological and pedagogical framework that integrates spiritual, intellectual, and physical dimensions into curriculum planning, classroom instruction, and school culture. The internalization of tauhid values is perceived to strengthen students’ intrinsic motivation, discipline, academic honesty, and learning engagement. Documentary data also indicate that the school demonstrates strong academic performance through AKM results and academic competitions. This study argues that TBIE can support academic achievement by shaping students’ self-regulation and learning character, although causal claims require further quantitative or longitudinal investigation. The study contributes to Islamic education scholarship by offering a case-based model of value-integrated learning that connects spiritual consciousness, character formation, and academic development.